Необходимые и достаточные условия существования и единственности ограниченных решений нелинейных дифференциальных уравнений - Слюсарчук, В. Е. (Нелінійні коливання, 1999)
Отриманi необхiднi та достатнi умови iснування i єдиностi обмежених розв’язкiв нелiнiйного диференцiального рiвняння dx/dt + f(x) = h(t), t ∈ R. Тут f : R → R — неперервне вiдображення, h(t) — неперервна i обмежена на R функцiя. Necessary and suf ficient conditions of the existence and uniqueness of bounded solutions of nonlinear dif ferential equation dx/dt + f(x) = h(t), t ∈ R, are obtained. Here f : R → R is continuous operator and h(t) is continuous and bounded function on R.